Produksi Naskah dan Mistisisme Aksara dalam Bhīma Svarga - Aditia Gunawan (Masyarakat Pernaskahan Nusantara, 2016)
As in other parts of Asia, the figure of Bhīma also been cult in Java. The popularity of this figure has been recorded in the spread of archaeological heritages such as inscriptions, statues, and reliefs, as well as textual legacies by Bhīma as the main character. The text that is discussed in this article, Bhīma Svarga, is one version of which 'might' contain the oldest text. This text was written in the 16th century and has never been satisfactorily studied. This text contains a dialogue between Bhaṭāra Guru and Bhīma who wants to save his father, Pāndu, from hell. All of Bhaṭāra Guru’s questions can be answered perfectly. The Bhīma’s answers is the core of the text, the doctrines of Śivaisme with many aspects of cosmological and philosophical. This article introduces the manuscript sources containing the text of Bhīma Svarga from the scriptorium of West Java that has been ignored in terms of Bhīma Svarga’s manuscript tradition in Bali. Additionally, this article also provides an overview of the production of manuscripts and meanings of the scripts at the time the text was written. === Seperti di belahan Asia yang lain, tokoh Bhīma pernah dikultuskan di Jawa. Popularitas tokoh ini terekam dalam sebaran peninggalan arkeologis seperti prasasti, arca, dan relief, maupun peninggalan teks-teks dengan Bhīma sebagai tokoh utama. Teks yang didiskusikan dalam artikel ini, Bhīma Svarga, merupakan salah satu versi yang ‘mungkin’ mengandung teks tertua. Teks ini ditulis pada abad ke-16 dan belum pernah diteliti secara memuaskan. Teks ini berisi dialog antara Bhaṭāra Guru dan Bhīma yang hendak menyelamatkan ayahnya, Pāndu, dari neraka. Semua pertanyaan dari Bhaṭāra Guru bisa dijawab dengan sempurna. Jawaban-jawaban Bhīma inilah yang menjadi inti dari teks, yaitu doktrin-doktrin Śivaisme serta aspek kosmologis dan filosofisnya yang kaya. Artikel ini memperkenalkan sumber-sumber naskah yang berisi teks Bhīma Svarga dari skriptorium Jawa Barat yang selama ini diabaikan dalam kaitannya dengan Bhīma Svarga dari tradisi pernaskahan Bali. Selain itu, artikel ini juga memberikan gambaran mengenai produksi naskah dan pemaknaan terhadap aksara pada masa teks tersebut ditulis.